Hydrolyzable tannins from Balanophora polyandra - Yangai Wang; Jianbo Yang; Aiguo Wang; Jie Ma; Jin Tian; Tengfei Ji; Yalun Su (Elsevier, 2013)
This study reports an investigation of the chemical constituents of Balanophora polyandra Griff. Fifteen compounds were isolated by column chromatography on silica gel, Toyo-pearl HW-40C, Sephadex LH-20 and by HPLC. Their structures were elucidated as 1,4-di-O-galloyl-2-O-[(E)-p-coumaroyl]-β-D-glucopyranose (1), 1-O-galloyl-β-D-pyranglucose (2), 1-p-coumaryl-β-D-pyranglucose (3), 1-O-(E)-caffeoyl-β-D-pyranglucose (4), 1,3-di-O-galloyl-β-D-pyranglucose (5), 1,6-di-O-galloyl-β-D-pyranglucose (6), 1-O-(E)-caffeoyl-4-O-galloyl-β-D-pyranglucose (7), 1-O-(E)-caffeoyl-6-O-galloyl-β-D-pyranglucose (8), 1-O-(E)-caffeoyl-4,6-di-O-galloyl-β-D-pyranglucose (9), 1-O-(E)-caffeoyl-4,6-(S)-HHDP-β-D-pyranglucose (10), 1,2,3,6-tetra-O-galloyl-β-D-pyranglucose (11), 4,6-(S)-hexahydroxydiphenoyl-(α/β)-D-glucose (12), 1-O-(E)-caffeoyl-4,6-[1',1"-(3',3",4',4"-tetrahydroxydibenzofurandicarboxyl)]-β-D-glucopyranose (13), flavogallonic acid (14), and phloretin-4'-O-β-D-glucoside (15) on the basis of spectral analysis. Compound 1 was a new hydrolyzable tannin, 9 was obtained from this genus for the first time, and compounds 5, 6 and 11-14 were isolated from this plant for the first time.